2002
DOI: 10.1080/00498250110085845
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4-mediated hepatic metabolism of the HIV-1 protease inhibitor saquinavirin vitro

Abstract: 1. The aim was to identify the major metabolites of saquinavir (SQV) from human hepatic microsomal incubations and the CYP isoform(s) responsible. 2. Ten fractions containing various metabolites were separated by isocratic reversed-phase HPLC and characterized by HPLC, mass spectrometry and NMR. 3. Metabolites were either mono- or di-hydroxylated derivatives of SQV. Fast-atom bombardment and electrospray MS showed that hydroxylation was predominantly situated on the decahydroisoquinoline ring. A major metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 17 publications
1
40
1
Order By: Relevance
“…No literature was identified on in vitro metabolism of ritonavir in rat hepatocytes, but in vivo and microsomal data published by Denissen et al (1997) and Kumar et al (1996) determined that metabolites M1, M2, M9, and M11 were the predominant primary metabolites, which agrees with observations in our work. Studies have been carried out in human liver microsomes at comparable substrate concentrations with the present study, and low K m estimates were reported: 0.61 and, 0.92 M for saquinavir (Eagling et al, 2002) and ritonavir (Koudriakova et al, 1998).…”
Section: Hepatocellular Uptake and Drug Metabolic Clearancementioning
confidence: 99%
“…No literature was identified on in vitro metabolism of ritonavir in rat hepatocytes, but in vivo and microsomal data published by Denissen et al (1997) and Kumar et al (1996) determined that metabolites M1, M2, M9, and M11 were the predominant primary metabolites, which agrees with observations in our work. Studies have been carried out in human liver microsomes at comparable substrate concentrations with the present study, and low K m estimates were reported: 0.61 and, 0.92 M for saquinavir (Eagling et al, 2002) and ritonavir (Koudriakova et al, 1998).…”
Section: Hepatocellular Uptake and Drug Metabolic Clearancementioning
confidence: 99%
“…Another five minority metabolites were found (Flitzsimmons, Collins, 1997). One of the major metabolites was subsequently identified as 6-equatorial-hydroxy-saquinavir (Eaglings et al, 2002).…”
Section: Protease Inhibitors (Pis)mentioning
confidence: 99%
“…Another five minority metabolites were found (Flitzsimmons, Collins, 1997). One of the major metabolites was subsequently identified as 6-equatorial-hydroxy-saquinavir (Eaglings et al, 2002).Biotransformation of indinavir (IDV) (Figure 14) takes place primarily in liver by CYP3A4 Lin et al, 1996), and can also occur in the small intestine. Oxidative metabolites were found in both in vivo and in vitro experiments using liver and intestinal microsomes of humans and rats (Chiba, Hensleigh, Lin, 1997).…”
mentioning
confidence: 99%
“…69 Currently, there appears to be a lack of studies demonstrating CYP450 expression in human T cells. As mentioned earlier, we did not detect any SQV degradants/ metabolites using our HPLC method.…”
mentioning
confidence: 99%